'The blind leading the blind' - A reflection on coaching blind football - David Mycock; Győző Molnár (European Federation of Adapted Physical Activity, 2021)
There are well-established links between successful athlete development, retention and high-quality coaching. Such links between athletes and coaches are also pertinent in disability sports. However, there is limited knowledge around coaching and coaches' needs and barriers in disability sport. To bridge this gap, a self-narrative approach was employed covering a 5-year period of the first author's career of coaching Blind (B1) and Visually Impaired (VI) football. This personal account provides a narrative, which identifies a range of key issues around the challenges of coaching practice in adapted football. Personal stories are presented through realist tales, which are grounded in the first author's lived experiences. Particular attention is paid to infrastructural challenges, which are evident in VI/Blind football. Based on the narratives presented, we reflect on the field-specific issues in B1 and VI football and make recommendations for practitioners.